Pelaksanaan Perjanjian Kerja Antara Pekerja Kontrak Dengan Bank Nagari - Atika Wulan Dari (RIO LAW JURNAL, 2021)
smoothness and progress of its business. In this effort, agreements arise for the progress and development of the company. However, in a work agreement, the position of the parties is often unequal. This unequal position turned out to have consequences for the agreement for a certain time. This is because the position of the employer is sometimes stronger than the worker so that the worker is in the category of the weak group. Conversely, if workers have dedication and professionalism in their fields, they will be stronger than employers in terms of wages. The implementation of the Work Agreement between Contract Workers and Bank Nagari is a Specific Time Work Agreement (PKWT) which in the implementation of the work agreement, the work agreement between contract workers and Bank Nagari is carried out for a period of 1 year and can be extended. In accordance with Law Number 13 of 2003 concerning Manpower. The form and content of the agreement/contract at Bank Nagari with contract workers are in writing. Meanwhile, in its implementation, contract workers are required to sign a work agreement that has been made by the Nagari Bank and is mutually agreed upon. As well as contract workers must also carry out their work in accordance with the Company's Operating Standards (SOP) that have been determined by the Bank. Keywords: Agreement, Employment Contract, Bank Nagari.     AbstrakBank Nagari dalam usahanya tidak terlepas dari kerjasama dengan pihak lain untuk mendukung kelancaran dan kemajuan usahanya. Dalam usaha tersebut, timbul suatu perjanjian-perjanjian demi kemajuan dan perkembangan perusahaan. Namun didalam perjanjian kerja, kedudukan para pihak sering tidak seimbang. Kedudukan yang tidak seimbang ini ternyata membawa konsekuensi pada perjanjian untuk waktu tertentu.  Hal ini dikarenakan kedudukan majikan adakalanya lebih kuat daripada pekerja sehingga pekerja berada dalam kategori golongan lemah. Sebaliknya apabila pekerja mempunyai dedikasi dan profesionalisme dalam bidangnya, maka akan lebih kuat dibanding majikan dalam hal pengupahan. Pelaksanaan Perjanjian Kerja antara Pekerja Kontrak dengan Bank Nagari ialah Perjanjian Kerja Waktu Tertentu (PKWT) yang mana didalam pelaksanaan perjanjian kerja tersebut , perjanjian kerja antara pekerja kontrak dengan Bank Nagari dilaksanakan dalam jangka waktu 1tahun dan dapat diperpanjang. Sesuai dengan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan. Bentuk dan isi perjanjian/kontrak di Bank Nagari dengan pekerja kontrak bersifat tertulis. Sedangkan pelaksanaannya, pekerja kontrak diharuskan menandatangani perjanjian kerja yang telah dibuat oleh pihak Bank Nagari dan disepakati bersama. Serta pekerja kontrak juga harus melaksanakan pekerjaannya sesuai dengan Standart Operasional Perusahaan (SOP) yang telah ditentukan pihak Bank. Kata Kunci: Perjanjian, Kontrak Kerja, Bank Nagari.